The Use of Andesite Rocks in the Hindu-Buddhist Kingdoms in Indonesia - Saputra, Yulian; Azmi, Muhammad; Kurniawan, Kurniawan (Yupa: Historical Studies Journal, 2024)
This research aims to explain the reasons for choosing andesite igneous rock as building material from Hindu-Buddhist kingdoms. The research method in this article uses four stages of historical research, namely; heuristic techniques, source criticism techniques, interpretation techniques, and historiography techniques. Data sources were collected through primary and secondary data. The four stages of this historical research method together with secondary primary data are then analyzed using a combination of historical geography to obtain an in-depth study. The results of the research illustrate that the use of andesite igneous rock was used for temple buildings, statues, relief sculptures, and writing from Pallawa to Ancient Java. The choice of andesite igneous rock during the Hindu-Buddhist kingdom was based on the quality of the rock. The quality of this andesite rock has high artistic value, gray in color, hard, chemical composition and specific texture that can be carved. The chemical composition is 57% -63% silica content with 6% alkali metal oxide content. The silica content of andesite igneous rock makes this rock material resistant to weathering.